Pemberdayaan Ekonomi Rumah Tangga Melalui Program Pelatihan Vokasional di Desa Nazalou Aloa Kecamatan Gunungsitoli Alooa Kota Gunungsitoli - Sepriman, Sepriman Gea; Laoli, Ardanalisman (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Vocational training is a community empowerment strategy aimed at increasing independence and household economic skills, particularly for women and youth. This activity was conducted in Nazalou Alooa Village, Gunungsitoli Alooa District, Gunungsitoli City. The program involved counseling, hands-on demonstrations, and independent practice, focusing on simple household product processing and sewing skills. The program demonstrated the active participation of 25 participants, with 18 successfully producing finished goods such as cloth masks and laundry soap, which were then marketed on a limited basis within the village. This activity aimed to improve practical skills and basic entrepreneurial knowledge, as well as motivation to start home-based businesses. This activity demonstrated that active community involvement in vocational training can be a crucial foundation for building a sustainable local economy based on village potential.